Intestinal P-glycoprotein Expression is Multimodally Regulated by Intestinal Ischemia-Reperfusion - Yusuke Terada; Jiro Ogura; Takashi Tsujimoto; Kaori Kuwayama; Takahiro Koizumi; Shunichi Sasaki; Hajime Maruyama; Masaki Kobayashi; Hiroaki Yamaguchi; Ken Iseki (Frontiers Media S.A., 2014)
Purpose. Reactive oxygen species (ROS) have multiple physiological effects that are amount-dependent. ROS are one of the causes of intestinal ischemia-reperfusion (I/R) injury. In this study, we investigated whether the amount of ROS and the degree of intestinal I/R injury affect the expression level of P-glycoprotein (P-gp). Methods. We used hydrogen peroxide (H2O2) as ROS in in vitro experiments. Intestinal I/R model rats, which were subjected 15-min ischemia (I/R-15), were used in in vivo experiments. Results. P-gp expression in Caco-2 cells was increased in response to 1 µM of H2O2 but decreased upon exposure to 10 mM of H2O2. We previously reported that P-gp expression is decreased after intestinal I/R with 30-min ischemia (I/R-30), which time a large amount of ROS is generated. I/R-15 induced slightly less mucosal and oxidative injury than did I/R-30. P-gp expression in the jejunum was increased at 1 h after I/R-15, and ileal paracellular permeability was increased. The blood concentration of tacrolimus, a P-gp substrate, was lower during 0-20 min but was higher during 40-90 min post-administration compared with that in the sham-operated rats. P-gp expression in the ileum was decreased at 6 h after I/R-15, due to abnormal localization of P-gp, resulting in a high blood tacrolimus concentration in rats reperfused for 6 h. Conclusions. ROS multimodally regulate P-gp expression depending on its amount. This is important for understanding the pattern of P-gp expression after intestinal I/R.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.